2014
DOI: 10.1098/rspa.2014.0074
|View full text |Cite
|
Sign up to set email alerts
|

Wave power extraction from a bottom-mounted oscillating water column converter with a V-shaped channel

Abstract: An analytical theory is developed for an oscillating water column (OWC) with a V-shaped channel to improve the pneumatic efficiency of wave energy extraction. An eigenfunction expansion method is used in a cylindrical coordinate system to investigate wave interaction with the OWC converter system. Auxiliary functions are introduced to capture the singular behaviours in the velocity field near the salient corners and cusped edges. Effects of the OWC dimensions, the opening angle and length of the V-shaped chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The harbor wall's resonating length can determine the water column's natural frequency, which is not effectively determined by its inclination. In Figure 5, the harbor wall's resonant length 𝑐/𝑏 at 1.5, supposedly the most optimum and efficient hydrodynamic characteristic was much closer to the recommended range proposed by Deng et al [66]. In random sea conditions, the RCW data appears to be consistent.…”
Section: Figure 5 Plan View Of Harbor Wall Opening Anglesupporting
confidence: 79%
“…The harbor wall's resonating length can determine the water column's natural frequency, which is not effectively determined by its inclination. In Figure 5, the harbor wall's resonant length 𝑐/𝑏 at 1.5, supposedly the most optimum and efficient hydrodynamic characteristic was much closer to the recommended range proposed by Deng et al [66]. In random sea conditions, the RCW data appears to be consistent.…”
Section: Figure 5 Plan View Of Harbor Wall Opening Anglesupporting
confidence: 79%
“…Approaches that achieving wave amplification in the field of wave energy utilization include i) wave reflection wall (Sarkar et al, 2015;Michele et al, 2016;Howe and Nader, 2017), ii) wave contraction wall (Miao et al, 2005;Lovas et al, 2010;Parmeggiani et al, 2013;Saadat et al, 2013 andDeng et al, 2014;Ram et al, 2016;Zhang and Ning, 2019), iii) projecting wall with wave resonance (Count, 1984;Ikoma et al, 2016;Daniel Raj et al, 2019) and iv) wave amplification bottom topography (Rezanejad et al, 2013;Rezanejad et al, 2019). Saadat et al (2016) proposed a novel Helmholtz Wave Energy Converter (HWEC), which amplifies the wave amplitude of a basin.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al (2013) employed the matched eigenfunction expansion method to study the structure optimization of a coaxial structure-supported OWC device, and presented the optimal bottom opening in the range of π/2-5π/4. Extending the work by Deng et al (2013) and Deng et al (2014) further established a theoretical OWC model with a V-shaped channel at the bottom. They concluded that the existence of the V-shaped channel can significantly increase the conversion efficiency and widen the range of highly effective wave frequencies.…”
Section: Introductionmentioning
confidence: 89%